2007
DOI: 10.1038/sj.bjc.6603727
|View full text |Cite
|
Sign up to set email alerts
|

In vivo inhibition of angiogenesis by sulphamoylated derivatives of 2-methoxyoestradiol

Abstract: Drugs that inhibit growth of tumours and their blood supply could have considerable therapeutic potential. 2-Methoxyoestradiol-3,17-O,O-bis-sulphamate (2-MeOE2bisMATE) has been shown to inhibit the proliferation of MCF-7 (ER+) breast cancer cells and angiogenesis in vitro. 2-MeOE2bisMATE and its analogue, 17-Cym-2-MeOE2MATE, were investigated for their ability to inhibit in vivo angiogenesis and tumour growth. The mouse Matrigel plug assay for angiogenesis was used to investigate the effect of compounds on neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 33 publications
1
55
0
Order By: Relevance
“…A novel oestrogen response element (ERE) has been found in the human BCRP promoter (Ee et al, 2004a, b), although it has also been suggested that oestradiol post-transcriptionally downregulates BCRP (Imai et al, 2005). Despite these observations, in this study the increased expression of BCRP in A2780.140 cells after long-term exposure to STX140 cannot be mediated by the ER as the A2780 cell line is ER negative and STX140 is non-oestrogenic (Chander et al, 2007).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…A novel oestrogen response element (ERE) has been found in the human BCRP promoter (Ee et al, 2004a, b), although it has also been suggested that oestradiol post-transcriptionally downregulates BCRP (Imai et al, 2005). Despite these observations, in this study the increased expression of BCRP in A2780.140 cells after long-term exposure to STX140 cannot be mediated by the ER as the A2780 cell line is ER negative and STX140 is non-oestrogenic (Chander et al, 2007).…”
Section: Discussionmentioning
confidence: 61%
“…As the IC 50 of STX140 in BCRPexpressing cells in vitro is only 1.5 -2 mM, this dose may be regularly or continuously exceeded in the in vivo model at a 20 mg kg À1 per day dose, resulting in good efficacy of STX140 in BCRP-expressing tumours in vivo. In addition to its antiproliferative properties, the anti-angiogenic qualities of STX140 also contribute to its efficacy in vivo, as STX140 has been shown to cause significant inhibition of angiogenesis when dosed at 10 mg kg À1 in a Matrigel plug assay (Chander et al, 2007) and at 20 mg kg À1 in xenograft models (Chander et al, 2007;Foster et al, 2008). This property would be unaffected by BCRP expression in the cancer cells of the tumour, adding to the efficacy of STX140 in BCRP-expressing tumours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MDA-MB-231 xenograft tumours were used to compare the in vivo efficacy of all three compounds, and a tumour resistance study was conducted to investigate the ability of STX243 to inhibit the growth of paclitaxel-resistant MCF-7dox40 xenograft tumours. The antiangiogenic potential of STX243 was also evaluated using an established Matrigel plug-based methodology (Passaniti et al, 1992;Prewett et al, 1999;Chander et al, 2007). To ascertain whether the biological properties of STX243 could overcome the oral bioavailability problems encountered with 2-MeOE2, the pharmacokinetics of STX243 were examined in adult female Wistar rats.…”
mentioning
confidence: 99%